State Responsibility Practices in Case of Human Rights Violation - Nurhidayatuloh; Idris, Akhmad; Febrian, Zulhidayata; Ikhsan, Rd Muhammad; Elmadiantini, Annalisa Ya; Afrilia, Dian; Tejomurti, Kukuh; Jaelani, Abdul Kadir; Handayani, Irawati; Zuhro, Fatimatuz (International Journal of Psychosocial Rehabilitation, 2020)
State responsibility in international law becomes a complex issue even since the mid-twentieth century until today. It is indicated by the absence of binding codification regarding the conception of responsibility of state in international law. Several attempts to codify this convention have been started since 1949 by the International Law Commission (ILC). To date, the final draft recognized is the 2001 ILC Draft which was embraced by the ILC at its fifty-third session, in 2001, and presented to the General Assembly as component of the Commission's report. As a draft, this instrument does not have a legally binding nature. But, international law experts believe that the principles contained are customary international law, especially those relating to states responsibility to human rights violations. This study is normative legal research examining the rules of international law on state responsibilities and human rights. Besides, the novelty of this research is stressing to the practice of state responsibility in factual cases, especially in human rights violation cases. The result of this research is that although the provisions in international law regarding the conception of responsibility of state are still a draft, in practice, several principles in the draft have been implemented by decisions in Regional Human Rights Courts and apply to countries in the regional scope.